Analisis Pemasaran Buah Naga (Hylocereus Undatus) Di Kabupaten Banyuwangi - Syamsul Hadi (STIE Mandala Jember, 2019)
Dragon fruit to be one of the flagship products Banyuwangi, but some patterns running inefficient marketing chains with an indication of some farmers receive farmer's share is less than 50% and most marketing agencies involved received benefits irrational. Least efficient marketing dragon fruit is determined by the length of the short marketing channels that lead further on the high and low cost marketing functions that must be removed. The objectives of this study were: 1) Tracing patterns dragon fruit marketing chains are awakened in Banyuwangi, and 2) to analyze margins, marketing efficiency, and elasticity of price transmission dragon fruit marketing. The type and method used in this research is descriptive and survey conducted in 2016 - 2017 some of the districts in Banyuwangi and Jember with sampling techniques through incidental and snowbolling sampling and data collection techniques in depth interviews and observations of the 32 respondents merchants, The results of this study concluded that: 1) Marketing of dragon fruits in the study area is formed of three patterns of chain marketing, where marketing agencies involved include, Small traders, merchant wholesalers, traders wholesalers, and retailers, each of which performs the function of different marketing, and 2) the results of the analysis of marketing margins dragon fruit showed that the pattern of the third chain is the most efficient marketing chain and patterns I chain most inefficient as indicated by the farmer's share of respectively 55.45% and 45%. The marketing price transmission elasticity Et dragon fruit (0.4) <1 or run inefficiently.